Development and Evaluation of Web GIS Application for Groundwater Management of Karanganyar Regency - Jumadi, Jumadi; Priyana, Yuli (Forum Geografi, 2015)
This research aims to develop and evaluate a geospatial application for groundwater resource management at Karanganyar Regency. The system development methodology from Whitten and Bentley (2007) was used in this research. To initiate the project, we discussed with the stakeholders from Karanganyar Regency which came from various related agencies followed by a focus group discussion (FGD) to analyse the system. Computational design and experiment were conducted to design the system prototype. Finally, we implement the system in the Regency. The result shows that the system is complex not only due to the managerial procedures but also the number of involved users (stakeholder) in the system. To address the emerged requirements from the FGD, we propose and develop a web-based GIS application with current open source technology and Google Map API which can be used for collaboration among stakeholders as well as for supporting the decision support purpose in the groundwater management. Currently, Air-tanah, the prototype of the application is available at http://geografi.ums.ac.id/air-tanah/. Both quantitative and qualitative evaluation of the system resulted good responses from the users.